An Intuitive Anesthesia Awareness of Contrast Media Administration - Sripunjun, Krongthip; Sombood, Pattharaporn; Vichitvejpaisal, Ruja; Vichitvejpaisal, Phongthara (Thai Journal of Anesthesiology, 2022)
Contrast media, an iodinated compound, is applied in diagnostic and interventional radiology. It helps the physicians correctly visualize the internal organs and effectively diagnose the abnormalities. In the limited situation, anesthetic personnel become a part of management team. Contrast media has some medicinal properties. Physicians should take a careful approach in patients with asthma, allergy to drugs or seafood, high serum creatinine, children below 1 year of age or under the weight, women with gestational age less than 4 months and patients continuing treated with radioactive iodine. Allergy to contrast media is a state of emergency. Concealed by anesthesia, patients’ signs and symptoms develop insidiously with skin lesion up to severe episode such as anaphylaxis or anaphylactoid reaction, which resulting in the loss of life. Treatments have to begin with opening patients’ airway, breathing with 100% oxygen, supporting hemodynamic and cardiac function, resuscitation and continuing care in the intensive care unit.